Perinephric fat stranding is associated with increased age and stone size but not with serum creatinine in patients with obstructing ureterolithiasis - Van Horn, Christine M.; Iovanel, Gregory; Atwater, Britney; Engelberg, Rachel; Sobieh, Ahmed; Sorokin, Igor (Urolithiasis, 2024)
Previous reports show increased severity of perinephric fat stranding (PFS) with elevated serum creatinine in obstructing ureterolithiasis. We sought to investigate this association with our institution’s patient population. We reviewed charts of patients diagnosed with obstructive ureterolithiasis or nephrolithiasis in our emergency department between January and October 2018. Patient demographics, lab results, and computed tomography (CT) imaging were reviewed. A blinded radiologist reviewed all CTs and graded hydronephrosis and PFS. Subjects were stratified by degree of PFS and compared via paired t-test, chi-squared test, univariate analysis, and multivariate analysis. We identified 141 patients; 114 had no-mild (Group 1) PFS, while 27 had moderate-severe (Group 2) PFS. Group 1 had a mean age of 56 (SD = 16.1) and mean stone size of 7.3 mm (SD = 4.22); 77% of the cohort had symptoms under 24 h. Group 2 was older with a mean age of 65 (SD = 16.2, p = 0.01) and mean stone size of 10.1 mm (SD = 6.07, p < 0.01); 50% had symptoms less than 24 h ( p = 0.01). PFS did not correlate with change in serum creatinine. Univariate and multivariate analysis showed increasing age increased the odds of moderate-severe PFS by 3.5% (OR = 1.035, p < 0.05) while increased stone size increased the odds of moderate-severe PFS by 13.7% (OR = 1.137, p = 0.01). Although increased PFS correlated with increased age and stone size, no correlation was found with presenting creatinine or change in creatinine. Degree of PFS is likely a poor predictor of renal disease severity in acute ureterolithiasis.